2011
DOI: 10.1111/j.1440-1746.2011.06733.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Golgi protein 73 expression in hepatocellular carcinoma tissue correlates with tumor aggression but not survival

Abstract: Significant overexpression of GP73 at both protein and mRNA levels along with overexpression of GP73 protein is associated with aggressive behavior of HCC, but not overall patient survival. Further research is needed to determine the potential of GP73 as a therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 19 publications
(54 reference statements)
6
57
2
Order By: Relevance
“…In a previous Chinese study, a significant correlation was identified between the overexpression of GP73 at the protein and/or mRNA levels and the aggressive behavior of HCC. However, no correlation was reported with the overall patient survival rates (22). In addition, Mao et al identified that GP73 may also be utilized for the surveillance of HCC recurrence in post-operative patients (17).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous Chinese study, a significant correlation was identified between the overexpression of GP73 at the protein and/or mRNA levels and the aggressive behavior of HCC. However, no correlation was reported with the overall patient survival rates (22). In addition, Mao et al identified that GP73 may also be utilized for the surveillance of HCC recurrence in post-operative patients (17).…”
Section: Discussionmentioning
confidence: 99%
“…One of the proteins identified in the serum of woodchucks with cancer and subsequently in the serum of people with HCC was golgi-proteins 73 (GP73). This protein has subsequently been analyzed in over 10,000 individuals with liver disease(Block et al, 2005b; Gu et al, 2009; Hann et al, 2010; Hu et al, 2010; Iftikhar et al, 2004; Jiang and Zhou, 2012; Liu et al, 2011; Maitra and Thuluvath, 2004; Malaguarnera et al, 2010; Mao et al, 2010; Mao et al, 2008; Marrero et al, 2005; Morota et al, 2011a; Ozkan et al, 2011; Riener, 2011; Riener et al, 2009; Schwegler et al, 2005; Shi et al, 2011; Sun et al, 2011; Tan, 2007; Tan et al, 2009; Tian et al, 2011; Wang et al, 2011a; Wang et al, 2009b; Wang et al, 2011b; Xu et al, 2011; Yamamoto et al, 2010; Zhao et al, 2010; Zhou et al, 2012) and for the most part, shown improved performance in the detection of HCC as compared to AFP. However, in several studies, GP73 either was either not elevated in HCC versus cirrhosis (Morota et al, 2011a; Riener et al, 2009) or was no better than AFP at differentiating HCC from cirrhosis.…”
Section: Glycomic Methodologies For the Identification Of Biomarkers mentioning
confidence: 99%
“…In a study aimed to investigate the expression of GOLPH2 and its correlation with clinical parameters, significant overexpression of GOLPH2 at either protein- or mRNA-levels or both were fund to be associated with aggressive behavior of HCC, but not overall patient survival [19]. This observation suggests that GOLPH2 is not merely a marker of HCC progression but it may have HCC-promoting activities.…”
Section: Golph2 In Liver Diseasesmentioning
confidence: 99%